Dificuldades da intubação submentoniana em pacientes com traumas faciais: scoping review - Cruz, Isabel Dutra da (2020)
Submental intubation consists of an airway maintenance technique that has its surgical access located in the medial / paramedial submental region, parallel to the base of the mandible. Its main objective is to replace nasotracheal intubation when it is impossible, appearing as an option to tracheostomy, which would be the next step in these cases. This article is a scoping review in order to describe the evidence in order to elucidate the difficulties encountered in submental intubation in facial trauma. The search strategy took place in the databases SciELO, LILACS,PubMed, The Cochrane Library, Web of Science, SCOPUS, CINAHL and Academic Search Premier (via EBSCO platform), Digital Library of Theses and Dissertations USP,USP Integrated Search and bank of CAPES theses, considering eligible primary studies, reviews, meta-analyzes and / or meta-syntheses, books and guidelines, theses and dissertations, published in indexed sources or in grayliterature and in Portuguese, English and Spanish. In the reviewed literature, 23 different groups of difficulties related to theprocedure were found. Among them, damage to the endotracheal tube and difficulty in passing the tube through the submental incision stand out as the most described. Therefore, the studies analyzed demonstrated a wide variety of difficulties related to several aspects intrinsically related to the performance of the submentonian intubation procedure